INTEGRASI PENDEKATAN SAINTIFIK MELALUI MODEL KECAKAPAN ABAD 21 PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Wildani Kushumah Auliya (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
The purpose of the study is to elaborate on the application of scientific approaches integrated with the 21st-century skills model in the learning of Pendidikan Agama Islam (PAI). Research methods use a qualitative approach with case study strategies in SMP 1 Kalasan State. Data collection is carried out by interviews with 2 teachers and some students in class VII, non-participant observations in learning activities, and documentation. The results show that the integration of scientific approaches with 21st-century skills models is realized through several stages: observe and assess it with critical thinking, collect information collaboratively and creatively, reason with critical thinking, collaborative and creative and interpret it with communicative. Forms of learning activities include reading material from various references, video views, religious activity practices, group discussions, and presentations in front of the class.